Promoting renewables and discouraging fossil energy consumption in the European Union - Cathrine Hagem (Statistics Norway, Research Department, 2010)
The European Union (EU) identified some positive and negative externalities related to energy production and consumption when adopting its Renewable Energy and Climate Change Package. Given these externalities, we derive the optimal combination of policy instruments. Thereafter, we explore the second-best outcome, given constraints on the use of some policy instruments, due to political considerations and international regulations. We show that the choice of policy instruments to promote renewable energy production (subsidies versus green certificates) affects the optimal level of energy consumption taxes. A second-best optimum for the EU cannot be achieved without a coordination of energy taxes and renewable energy policy instruments in each country, given the externalities addressed in this paper.
Keywords: D62; H21; H23; Q48; 330; climate policy; energy policy; green certificates; energy subsidies; energy ta